From deserts the prophets come: the creative spirit in Australia 1788-1972 - Serle, Geoffrey, 1922-1998. (Melbourne, Heinemann, 1973)
From Deserts the Prophets Come is a short history of literature, art, music, theatre, architecture, science and learning in Australia. It aims at providing an historical context for the growth of the arts, at bridging the gap between general historians and historians of the arts, and at providing historical perspective for the general reader interested in the creative arts in Australia. Dr Serle brings out to the full the remarkable rise in cultural standards and achievements in recent years; the greater part of the book deals with the last forty years. He discusses the problem of national- versus international- oriented art, and provides an overall theory of cultural growth in a 'new' country like Australia. 'If still from desetrs prophets come...' There has not been much 'savage and scarlet' yet, perhaps, but those who continue to talk in terms of a cultural desert in Australia are surely blind and dertemined to a do a perish. (Inside cover)
Index.
Bibliography: p. 237-260.
Keywords: Arts, Australian; Art; Settlement and contacts - Colonisation